PROSPECTS FOR THE IMPLEMENTATION OF INNOVATIVE BANKING PRODUCTS - INCENTIVE TO IMPROVE THE COMPETITIVENESS OF DOMESTIC BANKS - Timur Akimniyazov Bazarbaevich, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article studies the concepts of banking products and innovations, and analyzes the problems of introducing innovative banking products in domestic banks. Proposals have been developed on the prospects for introducing innovative products in banks.